2003
DOI: 10.1002/jbm.b.10048
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and simulator wear study of alumina ceramic THR to 17 years and beyond

Abstract: Three THAs with cementless monolithic alumina ceramic sockets and cementless Co-alloy stems were retrieved because of aseptic loosening after 17 and 24 years. At revision heads and cups were marked for orientation. Maps were drawn of wear patterns with the use of light microscopy and surveyed by SEM. In a simulator experiment 28-mm-diameter alumina heads and liners were used. The cups were mounted inverted in a hip simulator and run with calf serum as the lubricant. The hip loads were 2 kN maximum and a 1-Hz f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…There were also frequent reports of ''stripe'' wear across heads and around cup rims [15,54,62,71,77]. Our MoM retrieval studies noted similar stripe damage in retrieved MoM [6,9,10], although other groups disavowed their existence [34].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…There were also frequent reports of ''stripe'' wear across heads and around cup rims [15,54,62,71,77]. Our MoM retrieval studies noted similar stripe damage in retrieved MoM [6,9,10], although other groups disavowed their existence [34].…”
Section: Introductionsupporting
confidence: 58%
“…Retrieval studies of ceramic-on-ceramic (CoC) THA in particular have revealed ''normal'' wear mode produced by everyday activities as a circular wear pattern on the head and inside the cup [71,75]. There were also frequent reports of ''stripe'' wear across heads and around cup rims [15,54,62,71,77].…”
Section: Introductionmentioning
confidence: 99%
“…8 Simulators were programmed to provide a vertical distraction as well as a horizontal distraction during the swing phase, providing a simulation of the superior stripe wear created during walking ( Figure 1) and of the inferior stripe wear produced by other activities such as rising from a flexed position.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the nature of the femoral head might affect the wear of the polyethylene so a change to ceramic heads [15][16][17][18][19][20][21][22][23][24] was tested and has been instituted in many marketed devices. The use of ceramic-on-ceramic, in which both component materials are replaced by ceramic has also been tested and utilized in surgery [25][26][27][28] for several years. Metal-on-metal articulations initially had been used in the 1960s and 1970s [29,30] and have recently become attractive again as a possible solution to wear problems [22,[31][32][33][34][35][36][37][38].…”
Section: Open Accessmentioning
confidence: 99%